Perancangan Layout 3D Asset Dalam Pembuatan Komik Strip Minecraft Menggunakan Blender - Maria, Maria; hidayat, Nur (Politeknik Negeri Batam, 2024)
Minecraft Hub or MCHub is one of the divisions of PT. Pallas Bukit Batukaras which focuses on the media game Minecraft. In 2021, MCHub created a Minecraft comic strip as collaboration content and advertising about the game Minecraft, but stopped production in 2022. Based on an interview with the manager project, MCHub wants to return to making Minecraft comic strips and develop innovation with 3D style according to reference in the game Minecraft. Comic creation goes through pre-production, production and post-production processes. This research focuses on the production process stages layouting. Layout quality analysis uses qualitative model methods Miles and Huberman. This research produced 8 comic strips with each comic having 4 panels. The comic strip is published on the social media platform Instagram @minecrafthub_id.